ARSC 2021
DOI: 10.33492/arsc-2021
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the 2021 Australasian Road Safety Conference - Melbourne

Abstract: These proceedings describe research, educational and policing program implementation and policy and management strategies related to all aspects of road safety and especially related to the conference theme of Towards Zero: A Fresh Approach. The 2021 conference covers a comprehensive range of topics including speed, infrastructure and road design, education, licensing, vehicle design, impairment due to alcohol, drugs and mobile phones. The conference also presents innovative symposium sessions including interd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Moreover, the study found that the risk of serious injury is higher for pedestrians and cyclists who are aged over 65 years [6]. An additional research effort tried to assess the risk of injury or fatality resulting from pedestrian-bicycle collisions; the findings indicate that the probability of death is negligible, while the likelihood of injury is as infrequent as the probability of death in a plane crash [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study found that the risk of serious injury is higher for pedestrians and cyclists who are aged over 65 years [6]. An additional research effort tried to assess the risk of injury or fatality resulting from pedestrian-bicycle collisions; the findings indicate that the probability of death is negligible, while the likelihood of injury is as infrequent as the probability of death in a plane crash [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their statistical analysis leads to the conclusion that the risk of injury is higher for cyclists who collide with a motor vehicle, but collisions between pedestrians and bicycles can also lead to serious injuries, while the risk of serious injury is higher for pedestrians and cyclists aged over 65 years [7]. The same research team, a year later, published a study aimed at quantifying the risk of injury or death from pedestrian-bicycle collisions and concluded that the probability of death is almost zero, while the probability of injury is as rare as the probability of death in a plane crash [8]. A more recent study in Australia, specifically in Melbourne, focuses on pedestrian injuries due to collisions with bicycles, finding that, from 2006 to 2016, there was no increase and that the frequency of these injuries is extremely low, especially compared to the frequency of pedestrian injuries from a collision with a motor vehicle [9].…”
Section: Introductionmentioning
confidence: 99%